Dog Raising in Jorong Kapalo Koto Nagari Gantung Ciri Kubung Subdistrict, Solok Regency (Study Living Hadith) - Riri Maiyati; Rahma Ghania Alhafiza; Sarmida Hanum; Ismiati Ismiati (Institut Agama Islam Sumatera Barat, 2024)
This article aims to present the tradition of dog raising, the treatment of pet owners towards their pet dogs, and its implications on the community in Jorong Kapalo Koto, Nagari Gantung Ciri, Kubung District, Solok Regency. This research is a qualitative descriptive field research as a problem-solving procedure investigated by describing and depicting the condition of the subjects or objects of research based on visible facts or as they are in the field. This research is also based on living Hadith as it provides a unique and profound perspective on the phenomena being studied. This study will reveal and elaborate aspects such as the history or the origin of dog keeping in Jorong Kapalo Koto, the acquisition of pet dogs by the local community, the breeds preferred and abandoned, motivations for dog ownership, healthcare practices for ill dogs, dietary habits of pet dogs, waste management, and the overall influence of dog caregiving in Jorong Kapalo Koto. All these aspects are analyzed based on the teachings of Prophet Muhammad (Peace Be Upon Him). The findings of this research provide insights into the dynamics between religious teachings and daily practices in a local context, as well as the social implications of dog keeping in this rural Muslim community.